Odpowiedzi

2009-12-03T20:49:16+01:00
(x-5)²=(x-√3)(x+√3)
x^2-10x+25=x^2-3 /-x^2
-10x +25=-3 /-25
-10x=-28 /:-10
x=2,8

(x+1)²+(x-2)²=2(x-1)(x+1)
x^2 +2x+1 +x^2-4x+4=2(x^2-1)
2x^2-2x+5=2x^2-2 /-2x^2
-2x+5=-2 /-5
-2x=-7 /:-2
x=3,5

1-4(x+2)²=(1-2x)(1+2x)
1-4x^2+8x+16=1-4x^2 /+4^2
1+8x +16=1
17 +8x =1 /-17
8x=-16 /:8
x=-2

2009-12-03T21:07:40+01:00
G) (x-5)²=(x-√3)(x+√3)
x²-10x+25=x²-3
-10x=-3-25
-10x=-28 |:(-10)
x=2.8

h) (x+1)²+(x-2)²=2(x-1)(x+1)
x²+2x+1+x²-4x+4=2x²-2
-2x=-2-1-4
-2x=-7 |:(-2)
x=3.5

i ) (3x-4)²+4(2x+1)²=(5x+2)(5x+2)
9x²-24x+16+16x²+16x+4=25x²+10x+10x+4
(x na lewo liczby na prawo)
-28x=-16 |:(-28)
x=1.75

j) 1-4(x+2)²=(1-2x)(1+2x)
1-4(x²+4x+4)=1-4x²
1-4x²-16x-16=1-4x²
-4x²-16x+4x²=1-1+16
-16x=16 |:(-16)
x=-1

k) (3-2x)²+(x+4)(x-3)=5(x-2)²+7
9-12x+4x²+x²-3x+4x-12=5x²-20x+20+7
-12x-3x+4x+20x=20+7-9+12
9x=30 |:9
x=3.3333

l ) 2(x-0,2)²=x²+(x+0,1)²
2x²-0.8x+0.8=x² +x²+0.2x+0.2
-0.8x-0.2x=0.2-0.8
-x=-0.6 |:(-1)
x=0.6





  • Jajo
  • Początkujący
2009-12-03T22:07:49+01:00
H) (x+1)²+(x-2)²=2(x-1)(x+1)
(x²+1) + (x²-4)=2x-2(x+1)
x²+1 + x²-4=2x -2x -2
2x²-3=-2
2x²=-2+3
2x²=1/2
x²=½